PENGEMBANGAN GAME BUBBLE MATCH SEBAGAI MEDIA PEMBELAJARAN PEMBAGIAN DALAM BENTUK PENGURANGAN BERULANG UNTUK SISWA KELAS 2 SD - Meinita Yesi Anugrahini (Profesi Pendidikan Dasar, 2017)
This study aims to develop bubble match game as a medium of mathematics learning. This research focuses on the division material as a repeat reduction for grade 2 elementary students. Type of research used is Research and Development (RnD) model of ADDIE. The ADDIE development model has stages of Analysis, Design, Implementation and Evaluation. The subjects of this study are 2nd grade students of Elementary School Pangudi Luhur Ambarawa amounted to 37 students. Data collection techniques used are expert test / expert validation, test(multiple choice questions), non test (student response questionnaire and observation sheet). The effectiveness of this media was analyzed using Paired-Samples T Test conducted with SPSS  program while the prevalence of media was analyzed using expert test. From this research, it can be concluded that bubble match game media can be developed with ADDIE development model and proven effective with the increase of pretest average 81,62 while posttest 83,24. Media game bubble match proved valid based on validator’s judgment from media aspect that got score 4.1 with good category and from material aspect which got average score 3,9 with good category.